CAPITAL MARKET AND MONEY MARKET ONE ALTERNATIVES FOR FAMILY FINANCIAL MANAGEMENT DURING THE COVID-19 PANDEMIC IN THE COMMUNITY OF CAWANG KELURAHAN JAKARTA TIMUR - Yusuf Rombe (Politeknik Negeri Bengkalis, 2022)
ABSTRACTImplementation of Community Service activities held in the community in Cawang Village, East Jakarta in partnership with all 12th grade students of State Vocational High School 10 Cawang and State Vocational High School 64 Cawang, East Jakarta. The consideration for the appointment of SMK Negeri 10 Cawang and SMK Negeri 64 East Jakarta is to increase knowledge to prepare students who will complete their education at the high school level who will continue their education at the tertiary level or who will become entrepreneurs for beginners and millennial youth in the money market and capital market. , manage family finances so that they can develop well and manage family finances so that they can achieve certain funding targets in the future; and can protect and increase the wealth owned; in order to be able to manage cash flow (incoming and spending money); in order to be able to carry out risk management and manage risks properly. The method used is by conducting counseling about the money market and capital market and distributing online questionnaires to find out financial conditions during the COVID-19 pandemic. Based on the results of the questionnaire, most of the students of SMK Negeri 10 and SMK Negeri 64 Cawang, East Jakarta as well as several teachers and employees who participated in this PKM event, stated that this topic was very good in increasing family income and in general the participants hoped to be given more counseling. more about the money market and capital market on how to trade and choose and determine which money market and capital market instruments to trade. Keywords: family financial management, cash flow, trading, money market and capital market